Influence of honeycomb dimensions and forming methods on the compressive properties of beetle elytron plates. (January 2020) - Zhang, Xiaoming; Chen, Jinxiang; Okabe, Yoji; Zhang, Peiwei; Xiong, Xiaobing; Yu, Xindi
For developing lightweight and high-strength biomimetic sandwich structures, this study investigates the influence of honeycomb dimensions and forming methods on the mechanical properties of beetle elytron plates relative to honeycomb plates via compression experiments and the finite element method. The results indicate that the trabecular-honeycomb core structure in beetle elytron plates can increase the compressive strength by approximately 50% and double the energy absorption capacity of honeycomb plates with the same material costs. Furthermore, the influence of three types of forming methods on the compressive properties of beetle elytron plates is investigated by comparing the different deformation modes of these structures with those of honeycomb plates. Based on these findings, application recommendations regarding the forming methods of beetle elytron plates are presented to facilitate the structural design and preparation techniques according to the performance requirements of different fields, which will accelerate the industrial application of these biomimetic structures.